IoT-Enabled Bus Tracking System for Real-Time Campus Transportation - Bahrum, Ikhwan Hafiz; Puteh, Saifullizam; Muhammad Aiman,; Nur Anis Aqilah,; Ellya Maisarah,; Buhari, Rosnawati; Hortoyo, (Journal of Electronic Voltage and Application, 2025)
Transportation is a utilitarian means by which individuals may move from one location to another. In the present epoch of globalisation, transport plays a vital role in the economic development of a country. The statutory basis for accountability of a public service corporation is now ensuring the delivery of excellent and high-quality service. Currently, students, particularly those who do not have their own means of mobility, rely on school transportation to navigate the campus. However, an issue emerged when students were unable to retrieve the position and location while the bus was in motion. Users have difficulty due to the uncertainty of the bus's arrival schedule, which necessitates an indefinite waiting period. We developed an Internet of Things (IoT) based bus tracking system for Universiti Tun Hussein Onn Malaysia (UTHM) to resolve the problem. This system enables users to conveniently receive real-time information about the bus's current position, location, and estimated arrival time at each stop. The researcher used the Design Thinking Process (DTP) paradigm in this study. The process consists of five steps: empathy, deciding, ideation, prototyping, and testing. The analysis's results validate the successful development and planned operation of the system. Furthermore, the system has the capability to display the precise position and location of the bus, in addition to providing consumers with useful information. The accompanying questionnaire supports this claim, indicating that 32 students, which accounts for 95% of the target audience, have confidence in the product's ability to work well. Ultimately, the IoT-enabled bus tracking system implemented at UTHM effectively accomplished all of its predetermined objectives.